2019
DOI: 10.3390/d11120234
|View full text |Cite
|
Sign up to set email alerts
|

Tree Diversity Reduces Fungal Endophyte Richness and Diversity in a Large-Scale Temperate Forest Experiment

Abstract: Although decades of research have typically demonstrated a positive correlation between biodiversity of primary producers and associated trophic levels, the ecological drivers of this association are poorly understood. Recent evidence suggests that the plant microbiome, or the fungi and bacteria found on and inside plant hosts, may be cryptic yet important drivers of important processes, including primary production and trophic interactions. Here, using high-throughput sequencing, we characterized foliar funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 115 publications
(123 reference statements)
5
15
0
Order By: Relevance
“…On average, however, the infestation rate of the fungal pathogens was not significantly affected by tree species richness at the plot level. Thus, our study is in line with former studies in forests where pathogen load was not related to the number of host species within a tree community (Hantsch et al., 2013), and it contradicts studies that found a decrease in fungal richness with increasing tree richness at the plot scale (Griffin et al., 2019). It might well be that the dilution effects were blurred by specific responses of pathogens associated with particular tree species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On average, however, the infestation rate of the fungal pathogens was not significantly affected by tree species richness at the plot level. Thus, our study is in line with former studies in forests where pathogen load was not related to the number of host species within a tree community (Hantsch et al., 2013), and it contradicts studies that found a decrease in fungal richness with increasing tree richness at the plot scale (Griffin et al., 2019). It might well be that the dilution effects were blurred by specific responses of pathogens associated with particular tree species.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to the analysis at the plot level, both fungal pathogen richness and fungal pathogen infestation decreased with increasing tree richness at the tree species level. Such a negative relationship was shown before for fungal richness at the neighbourhood scale (Griffin et al, 2019). In this study, we found a weak but significant effect of tree species richness on fungal pathogen infestation, indicating that the same tree species suffered less pest damage in heterospecific mixtures than in monocultures.…”
Section: Individual Tree Species Effects On Foliar Fungal Pathogen Risupporting
confidence: 74%
“…The diversity data presented here must be taken with care because diversity estimates and comparisons must take into account various factors, such as plant organ sampled (leaf, stem, or roots), number and type of plant taxa (Gamboa et al 2003), differences in sampling intensity and strategy (Arnold 2007), type of environments, if endophytes are slow or fast growers, and type of culture media. These findings support the generalized view that botanical richness may promote a corresponding hyperdiversity in endophytic fungi, arguments opposing the view that an increase in tree richness and phylogenetic diversity will show an increase in fungal species can be taken from an experimental temperate forest study by Griffin et al (2019) but are out of the scope of our review.…”
Section: Fungal Endophyte Diversitysupporting
confidence: 83%
“…The concept of a hidden hyperdiversity (Smith et al 2008) of endophytic fungi in tropical ecosystems of the Amazon basin and, accordingly, the potential of chemical diversity have been highlighted by various authors (Kharwar et al 2011;Rundell et al 2015). Few studies have been published to date that show that tropical forests have some of the highest levels of foliar and stem-inhabiting fungal endophyte diversity (Arnold and Lutzoni 2007;Griffin and Carson 2018;Rundell et al 2015). These have been scarcer in mega-biodiverse environments (Rundell, 2015).…”
mentioning
confidence: 99%
“…Such diversity is influenced by the high diversity of forests present in the sampling sites, which certainly influences the symbiosis between orchids and fungi. Additionally, several exogenous mechanisms related to the ecosystem can influence the composition of endophytes, including the mycoheterotrophic strategy of the plant (autotrophic, fully or partially mycoheterotrophic), nutrient availability and surrounding plant species [33,34]. Similar to our study, Fracchia et al [35] analyzed the potential of mycorrhizal fungi isolated from the terrestrial Andean orchids, Chloraea riojana and Aa achalensis, for promoting seed germination in threatened species.…”
Section: Discussionsupporting
confidence: 69%